Effect of Foliar Spray of Plant Growth Regulators and Optimum Planting Ratio on Seed Quality in CGMS Based Chilli Hybrid UARChH42 (JCH 42) - NEHA THAKUR; SN VASUDEVAN; SR DODDAGOUDAR; SANGEETA I MACHA (Seed Research, 2026)
In the present investigation the seed production in newly released chilli hybrid was carried out while studying the effect of planting ratio (2:1 was best) and PGR spray (NAA @ 40 ppm best) on seed quality parameters viz., germination (%), seedling dry weight (mg) shoot length (cm), seedling vigour index, dehydrogenase enzyme activity and lower electrical conductivity (dS cm-1) as compared to other treatments. Also the treatment combinationP2S4 (2:1 + NAA @40 ppm) proved to be the best. This treatment combination resulted in higher values of these parameters as well. Thus the parental lines in 2:1 ratio proved to be best for natural crossing followed by spraying at flower initiation stage with NAA @ 40 ppm as PGR to obtain higher seed quality in CMS based chilli hybrid UARChH42 (JCH42).